Demonstration of a chipless harmonic tag working as crack sensor for electronic sealing applications. Issue 2 (2nd October 2015) - Palazzi, Valentina; Mariotti, Chiara; Alimenti, Federico; Virili, Marco; Orecchini, Giulia; Mezzanotte, Paolo; Roselli, Luca
Abstract : This work proposes a chipless radio frequency identification approach based on the working principle of the harmonic radar. A frequency multiplication stage is performed by a non-linearity (i.e. a Shottky diode) on the tag in order for the tag answer to be insulated from the interrogation signal, thus avoiding the need for clutter cancellation techniques. Firstly, the performance of a simple one-bit harmonic tag relying on a low-power frequency doubler is analyzed and then a novel crack sensor, implemented by adding a disposable band-stop filter, is presented. Both solutions demonstrate tag-to-reader operational distances beyond 1 m. The characterizing blocks (namely the frequency doubler and the filter) are fabricated on cellulose substrates (i.e. regular photographic paper), thus being conformal to their implementation for applications in the new paradigm of Internet of Things.